Multicultural Education and Gender Equality as an Effort in Overcoming Sosiocultural Diversity - Zahratul Azizah; Neviryani Neviryani (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
The diverse conditions of society, both language, religion, and ethnicity, make the Indonesian nation a pluralistic country. This plurality is a nation's potential, but on the other hand it will boomerang that will trigger conflicts everywhere that will harm all parties if they cannot control it. Various conflicts can occur only because of differences in ethnicity, ethnicity, language, religion and culture. In addition, the issue of gender inequality is also one of the problems that exist in our country. There are still many discriminatory treatments against one gender, especially women, such as the opportunity to obtain equal rights in the economy, education, politics and society, the stigma attached to women who can only work in the domestic sphere, treatment of acts of violence, even to the role of woman must bear in order to meet the needs of her life. This paper aims to review the importance of multicultural education and gender equality in overcoming the problem of sociocultural diversity. The research method used is a literature study, which explains the phenomena that occur based on scientific studies that have been carried out previously. Therefore, there is a need for multicultural education efforts and gender equality in order to eliminate the differences that occur in society so as to make life full of peace and toleranceKeywords: Multicultural education, gender, sosiocultural diversity